Analisis Produktifitas Alat Berat Concrete Paver Pada Pekerjaan Rigid Pavement Proyek Pembangunan Jalan Tol Jakarta-Cikampek II - Riztira Yeca Tiya Milleda; Budi Priyanto (Politeknik Negeri FakFak, 2022)
Every toll road project development will require heavy equipment to facilitate work, one of which is rigid pavement work. Rigid pavement is a pavement construction using aggregate as raw material and using cement as a binder, so it has a relatively high level of stiffness, especially when compared to asphalt pavement (flexible pavement), so it is known and referred to as rigid pavement. The tool used for rigid work is the concrete paver, this tool is used because it is more efficient and can maintain the quality of the concrete. This study aims to be able to determine the productivity of the concrete paver heavy equipment. The data used is in the form of primary data obtained by observation, interviews and field data as well as manual calculations. The results obtained are the productivity of concrete paver heavy equipment with rigid work along 180 m wide 6, 7 is 43,5 while the ready mix productivity is 42.8 m³/hour with a production time of 6 hours 20 minutes.